Pony feeding management: the role of morphology and hay feeding methods on intake rate, ingestive behaviors and mouth shaping - Bordin, Clara; Raspa, Federica; Greppi, Martina; Harris, Patricia; Ellis, Andrea Dorothea; Roggero, Angela; Palestrini, Claudia; Cavallini, Damiano; Bergero, Domenico; Valle, Emanuela (Frontiers in Veterinary Science, 2024)
In the last decade, haynets and slow feeders have been promoted as sustainable tools to improve the feeding management of horses and to reduce the forage waste, however, little is known about their effects on ponies. Therefore, the aim of this study was to analyse the effects of different hay feeding methods on ingestive behaviours, intake rate and mouth shaping of ponies belonging to two breed types, and thus characterized by different head morphology. Shetland type (SH, n=5) and Welsh/Cob type (WC, n=4) ponies were fed hay using four feeding methods: on the ground (G), a fully filled haynet (HF), a partially filled haynet (HL), and a slow-feeder hay box (HB). The head morphology was measured for each pony. Subsequently video recordings were obtained to apply geometric morphometrics and to perform behavioural analysis. The intake rate was measured per each pony and each feeding method. Data obtained with geometric morphometrics were analysed using principal component analysis (PCA) and canonical variate analysis (CVA). Behavioural data and intake rate measurements were analysed performing a mixed model, a post-hoc Tukey's test, a Pearson's correlation test, and a stepwise regression model. The geometric morphometrics results demonstrated that all feeding methods influenced the mouth shaping altering the intake rate. Differences in mouth shaping and ingestive behaviours of SH and WC ponies confirmed the role of morphology even in the feeding management.The HL proved to be the most effective tool to increase the feeding consumption time when needed, even if the HB may be the optimal choice to reduce the intake rate maintaining a natural posture. Future studies are suggested to fully understand how body size and morphology influence nutrition in the equine species.